Variation in Ringed Seal (Pusa hispida) Density Along a Latitudinal Gradient of Sea‐Ice Conditions - Cody G. Carlyle; James D. Roth; Brent G. Young; David J. Yurkowski; Christine Michel; Steven H. Ferguson (Ecology and Evolution, 2025)
ABSTRACT Anthropogenic climate warming is triggering poleward species redistributions, highlighting the importance of understanding how species distributions and abundance vary along latitudinal gradients. Ringed seals (Pusa hispida) rely on sea ice as habitat during key periods of their life history and inhabit a broad latitudinal range with diverse sea‐ice conditions, making them a model species to study patterns in density along a spatial–environmental gradient. We estimated the density of ringed seals from systematic aerial surveys along a latitudinal gradient in the eastern Canadian Arctic to investigate the response of ringed seals to regional variation in sea‐ice conditions. Ringed seals exhibited similar densities at our low (58.8° N; 2017: 0.46 ± 0.11 seals/km2) and intermediate latitude (72.7° N; 2016: 0.70 ± 0.14 seals/km2; 2017: 0.45 ± 0.07 seals/km2) regions. In contrast, observed ringed seal densities (2018: 0.05 ± 0.01 seals/km2; 2019: 0.09 ± 0.01 seals/km2) in the high‐latitude region (82.5° N) were an order of magnitude lower. This shift is concurrent with the transition in ice conditions from predominantly first‐year ice (85.0% concentration) at the low‐latitude region to primarily multiyear ice (86.8% concentration) at the high‐latitude region. These findings indicate that the variation in icescapes across the ringed seal's vast range likely has an influence on their density. We propose that ringed seal densities at higher latitudes are limited by multiyear ice, which is less suitable for construction of undersnow lairs and breathing holes. The shift in sea‐ice conditions may also have consequences for biological productivity that supports their diet. Our results suggest a nonuniform response of ringed seals to ongoing sea‐ice recession across the Arctic. Ringed seal densities could increase with a shift from multiyear to first‐year ice at higher latitudes and simultaneously decline with a transition from first‐year ice to open water at lower latitudes.